2016
DOI: 10.1016/j.sbspro.2016.05.120
|View full text |Cite
|
Sign up to set email alerts
|

Using Six Sigma Methodology to Improve the Assembly Process in an Automotive Company

Abstract: The exigencies of the permanently evolving markets require continuous adaptation of company offers. The development and continuous improvement of the quality and environment management systems would be to anticipate these developments and therefore fully satisfy the needs and expectations of each partner (customers, staff and other stakeholders) and also maintain competitive advantage. One of the possibilities of gaining operational excellence is implementing different quality improvement initiatives like Tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 0 publications
0
24
0
5
Order By: Relevance
“…This study indicated that the general working condition factor has the greatest impact on the level of satisfaction, compared to the other indices [21]. Pugna, Negrea, and Miclea present a creative solution to improve an assembly process in an automotive company through the use of SS, Pugna et al, mentions the desire to achieve business excellence in the automotive industry and assumes the commitment to develop and deliver perfect solutions, products or services, promoting the production philosophy Zero defects and considers that SS is the best way to achieve quality and reduce waste by helping organizations to produce better products and services, faster and cheaper [22].…”
Section: Process Improvementsmentioning
confidence: 99%
“…This study indicated that the general working condition factor has the greatest impact on the level of satisfaction, compared to the other indices [21]. Pugna, Negrea, and Miclea present a creative solution to improve an assembly process in an automotive company through the use of SS, Pugna et al, mentions the desire to achieve business excellence in the automotive industry and assumes the commitment to develop and deliver perfect solutions, products or services, promoting the production philosophy Zero defects and considers that SS is the best way to achieve quality and reduce waste by helping organizations to produce better products and services, faster and cheaper [22].…”
Section: Process Improvementsmentioning
confidence: 99%
“…As one of railway manufacturing company in Southeast Asia, quality is an important factor in maintaining customer satisfaction and one of the key success in business competition [1]. Also, this railway manufacturing company has to improve its quality, which is the products that have been produced must be zero defects [2]. The core product of this railway manufacturing company is train.…”
Section: Introductionmentioning
confidence: 99%
“…Balanced Scorecard Method focused on strategic organization management [12]. Six Sigma Method focused on permanently improving all organization processes and eliminating procedural errors [13].…”
Section: Introductionmentioning
confidence: 99%